1981
DOI: 10.1126/science.7268421
|View full text |Cite
|
Sign up to set email alerts
|

Central Norepinephrine Metabolism During Alcohol Intoxication in Addicts and Healthy Volunteers

Abstract: The concentrations of the major norepinephrine metabolite, 3-methoxy-4-hydroxyphenylethylene glycol (MOPEG), in lumbar cerebrospinal fluid of alcoholic patients were markedly elevated during intoxication and successively declined during 1 and 3 weeks of abstinence. During intoxication the MOPEG concentration in cerebrospinal fluid showed a statistically significant correlation with the blood alcohol concentration. In healthy volunteers who received 80 grams of ethanol, the MOPEG concentration in cerebrospinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
2

Year Published

1982
1982
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(32 citation statements)
references
References 11 publications
2
28
0
2
Order By: Relevance
“…We thus wanted to examine if stressful manipulations, which would increase adrenergic tone in vivo, could alter the expression of α 1 -AR LTD ex vivo. Withdrawal from alcohol intoxication has been shown to increase anxiety (40), and patients experiencing withdrawal have elevated levels of NE and its metabolites (36,41). Furthermore, CIE can increase anxiety-like behavior in animal models (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus wanted to examine if stressful manipulations, which would increase adrenergic tone in vivo, could alter the expression of α 1 -AR LTD ex vivo. Withdrawal from alcohol intoxication has been shown to increase anxiety (40), and patients experiencing withdrawal have elevated levels of NE and its metabolites (36,41). Furthermore, CIE can increase anxiety-like behavior in animal models (44).…”
Section: Discussionmentioning
confidence: 99%
“…Stress disorders and alcoholism are highly comorbid (35). Data from human studies suggest that NE is increased in the central nervous system (CNS) of alcoholics (36), where it may play a role in the pathogenesis of alcoholism (35). Additionally, the adrenergic system remains an attractive target for intervention in alcoholism (11).…”
mentioning
confidence: 99%
“…Their higher BELs indicated that the higher habitual alcohol intake has not led to faster metabolism of etha nol as might be expected [56,57] but rather confirms observations from other studies that either no [ 18,58] or even positive relationships may be observed between amount of voluntary intake of alcohol and BEL upon acute exposure in animals [59] or men [60] possibly due to faster absorption to peak levels [61] supporting a genetically determined rate of metabolism [62,63] which has been shown to be a stable individual charac teristic [64], Lower fluid-induced NE release in HC may again be taken as evidence for lower noradrenergic responsiveness to a physical stimulus as observed with venipuncture, and a negative correlation between BEL and NE increase in the HC ethanol group (r = -0.54, p < 0.05) may, in addition, indicate tolerance of the norad renergic system to ethanol (since acute intake would induce dose-dependent increases of central nervous NE turnover in nontolerant subjects, as demonstrated by CSF analyses in healthy volunteers [65,66], But also lower respective baseline NE brain metabolism (turn over in CSF or DBH in plasma) observed in subjects with higher habitual alcohol intake [65,67] or with higher sensation seeking scores [30] would support the observation of a reduced general noradrenergic turnover in high alcohol consumers.…”
Section: Discussionmentioning
confidence: 99%
“…При нормальном состоянии альфа 2 рецепторы ингибируют работу пресинап тического норадреналового нейрона. При абстинентном синд роме альфа 2 рецепторы становятся менее чувствительными, что приводит к неспособности норадренергичекой системы регулировать свою работу [62,63]. Многочисленные исследо вания подтверждают эффективность применения перораль ного и трансдермального клонидина (старейшего альфа 2 агониста), в снижении симптомов синдрома отмены, относя щихся к симпатической активации (особенно гипертензии и тахикардии) [64].…”
Section: распознание и лечение алкогольного абстинентного синдрома в unclassified